Реализация концепта „доверие/недоверие” в контексте польско-российских отношений (на материале статьи газеты „Gazeta Polska”) (Heteroglossia – studia kulturoznawczo-filologiczne, 2021)
In order to get closer to the answer to the question whether Russians and Poles trust each other, the author of this research resorts to linguocultural analysis. Based on the article Gazeta Polska the author attempts to find out how close the concept of Russia and the concept of trust could be. By analysing the linguistic units and means used in the article, the author comes to the conclusion that the concepts of Russia and trust do not overlap within the discourse of this newspaper. This conclusion is drawn from the fact that in the Gazeta Polska article the concept of Russia is concentrated around negative evaluative components. In addition, the author finds that the language units and techniques used in the text of the article are intended to arouse feelings of fear as well as emotions of indignation, outrage and disagreement in the reader.